Notes about the contest of infractions in Administrative Disciplinary Law: Peruvian case - Jiménez Alemán, José Alonzo (2018)
This article develops the institution of the concurrence of infractions in the scope of Administrative Sanction Law, in order to specify the extension of the institution regarding to the regulations. For these purposes, the author presents a detailed analysis, taking as reference the development of the criminal law and the comparative experience in the matter of Administrative Sanction Law. Finally, in order to clarify the concepts, two specific administrative pronouncements are analyzed.